Comparative Analysis of Load Factor Method Static and Dynamic Method (Case Study Akdp Bus Route Rajabasa - Bakauheni) - A. Ikhsan Karim; Ahmad Zulkily (International Conference on Engineering and Technology Development (ICETD), 2013)
Along with the increasing mobility of the population, then the users are demanding the availability of inter-city transportation are eligible smoothness, comfort and safety. It is also worth noting that the operator provides services angkutan.Operator certainly will not be able to serve well if not achieving the target of economic benefits. This is closely connected with the passenger load factor on a given route. To get a load factor (load factor) are known methods of static and dynamic methods. Each of these methods have shortcomings and kelebihannya.Trayek Rajabasa - Bakauheni AKDP bus served an important tool in making the transportation of passengers from Sumatra towards Java. So for performance that will be investigated how the operator is indicated by factors muatnya.Penelitian intends to see bus load factors, by comparing the static method with dynamic survey methods on the route that serve transportation between cities in the province that connects the city of Bandar Lampung in the South Lampung is also the gateway to the island Jawa.Dari analysis and calculations obtained by the method of static load factor LF values obtained Sunday morning at 45.33%, while the evening LF obtained a value of 24.44%. LF Monday morning at 39.11%, while the LF night obtained a value of 35.11%. From the analysis and calculation of Dynamic Methods for directions Rajabasa - Bakauheni obtained Load Factor on Sunday morning at 57.09%, while the evening LF obtained a value of 31.70%. LF Monday morning at 55.98%, while the LF night obtained a value of 46.98%. For directions Bakauheni - Rajabasa obtained Load Factor on Sunday morning at 63.31%, while the evening LF obtained a value of 36.35%. LF Monday morning at 61.50%, while the LF night obtained a value of 53.95%. Regression analysis of the results obtained equations that represent relationships Static and Dynamic Load Factor direction Rajabasa - Bakauheni is: y = -3.859 + 3.955 x x2 - 0.422, the value of coefficient of determination, R ² = 0,972. As for the direction of Bakauheni - Rajabasa equation: y = -4.677 + 4.585 x x2 - .479, with a value of R ² = 0.988